2021
DOI: 10.18844/cjes.v16i1.5523
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Grade R teachers’ mathematics curriculum practices and strategies for improvement: Implications for physics teaching

Abstract: This study sought strategies to improve teachers’ professional curriculum practices in a Grade R mathematics class. A phenomenological research design was employed to generate data for the study using a sample of fifteen participants. A semi-structured interview guide was used to collect the data for the study. In this regard, the interview guide was properly validated, and trial tested. Data collected for this study were analysed using a thematic analysis. The findings of the study showed that the strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As a result of this poor implementation of the teenage mothers' school re‐entry policy, most of them pass through a lot of hardship in school while the majority drop out of school. These findings despite that they are the first in the study area, compare with the findings of similar studies in other African countries such as Mwanamwambwa (2017), Joase (2018), Mulenga and Mukaba (2018), Lebele (2018), Musili, Mulwa, et al (2020), Mpayipheli and Kheswa (2020), and Barmao‐Kiptanui (2020), Musili, Mwania, et al (2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a result of this poor implementation of the teenage mothers' school re‐entry policy, most of them pass through a lot of hardship in school while the majority drop out of school. These findings despite that they are the first in the study area, compare with the findings of similar studies in other African countries such as Mwanamwambwa (2017), Joase (2018), Mulenga and Mukaba (2018), Lebele (2018), Musili, Mulwa, et al (2020), Mpayipheli and Kheswa (2020), and Barmao‐Kiptanui (2020), Musili, Mwania, et al (2020).…”
Section: Discussionsupporting
confidence: 86%
“…Mpayipheli and Kheswa (2020) revealed that there are difficulties in the implementation of the teenage women's re‐entry policy in South Africa, due to lack of in‐service training, lack of resources to provide remedial and psychological services to pregnant learners, unclear school policies among others. The implementation re‐entry policy of teenage mothers in Kenya was partially successful due to the presence of small numbers of teenage mothers in school compared to those who dropped out due to pregnancy (Barmao‐Kiptanui, 2020). Implementation of the readmission policy of girls after a teenage pregnancy is affected by the guidance and counseling sessions, principals' opinion, and community support (Musili, Mwania, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By employing phenomenology, we were able to openly and continuously consider the impact that our preconditions and assumptions may have on the study process. This design has been adopted by Thwala et al (2020), Thwala et al (2022), Nhase et al (2021), Baloyi-Mothibeli et al (2021, Gqoli et al (2022), Gqoli et al (2023).…”
Section: Methodology: a Qualitative Phenomenological Research Designmentioning
confidence: 99%
“…When children are playing, as shown by Strauss (2015), they create ideas, feel safe and make sense of their previous ideas of what they experience. However, Baloyi-Mothibeli et al (2021) found that numerous difficulties have been encountered in the teaching and learning of mathematics in South African foundation schools. This is clear from pupils' low mathematics performance, which has recently attracted a lot of attention (Umugiraneza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%